O consumo público de eventos esportivos: um olhar para além dos estádios de futebol - Almeida, Erick Bastos de (2014)
The present study investigated the public consumption of live sporting events inside and outside the scope of stadiums. The main goal of the study was to determine if the fan (supporter), perceives a relation of substitution or complementarity between the favorable attitudes towards attendance at the stadium or at other public places to watch football games. Additionally, the study aimed to investigate the influence of the identification of a sports fan (supporter) with his team in the attitude and public consumption of the spectacle of soccer in the stadium or in other public places, as well as if demographic characteristics (gender and age group) exert some kind of moderating effect on the relationships studied. To address these issues we sought reference in SIT - Social Identity Theory and SCT - Self-Categorization Theory. A survey was conducted, targeting supporters of the four main soccer teams from Rio de Janeiro, through assisted structured interviews. The sample was intentional and of convenience and data collection totaled 507 valid questionnaires. Data analysis was performed in two stages. The first contemplating an exploratory factor analysis, which aimed at the preliminary observation of the quality of the scales. The second stage included a confirmatory factor analysis in order to purify the scales. Convergent, discriminant and nomological reliability and validity of the constructs were evaluated. To test the substantive hypotheses of the study the structural equation modeling technique and multigroup analysis were used. The analysis results allowed empirical support of three out of the five substantial hypotheses. The results suggest that (a) The identification of the fan with the team exerts a positive influence on the attitude towards watching games at the stadium; (b) The favorable attitude of fans towards the stadium exerts a positive influence on the attendance at the stadium; and (c) The favorable attitude of fans towards public places exerts a positive influence on attendance at public places. However, we could not fully support the hypothesis that (d) identification of the fan with the team influences the attitude towards public places; and (e) The attitude of fans towards the stadium influences the attitude towards public places. The moderating effects of gender and age group were also not supported.